2003
DOI: 10.1046/j.1467-789x.2003.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of obesity: an update on anti‐obesity medications

Abstract: The information presented in this article provides an overview of physiological agents, therapeutics in current use, and medications that have been extensively used in the past but are no longer available, or are not classically considered as anti-obesity drugs. The authors present an extensive review on the criteria for anti-obesity management efficacy, on physiological mechanisms that regulate central and/or peripheral action energetic homeostasis (nutrients, monoamines and peptides), and on beta-phenethylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0
8

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 127 publications
1
59
0
8
Order By: Relevance
“…At present, only two drugs are approved for the long-term treatment of overweight patientsFsibutramine and orlistat. 4,5 Appetite-suppressant drugs, by reducing overall hunger sensation, can help obese patients diminish weight. 6 Despite apparent differences in pharmacology and abuse potential, there is still a tendency to refer to all centrally acting sympathomimetic appetite suppressants as 'amphetaminelike' and to view them all with equal harm potential.…”
Section: Introductionmentioning
confidence: 99%
“…At present, only two drugs are approved for the long-term treatment of overweight patientsFsibutramine and orlistat. 4,5 Appetite-suppressant drugs, by reducing overall hunger sensation, can help obese patients diminish weight. 6 Despite apparent differences in pharmacology and abuse potential, there is still a tendency to refer to all centrally acting sympathomimetic appetite suppressants as 'amphetaminelike' and to view them all with equal harm potential.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19] A good recent metaanalysis about pharmacologic treatment of obesity could not present pooled analyses of fluoxetine treatment, because the statistical tests and Forest plot of individual study results revealed too much heterogeneity. However, in six of the seven studies, significant weight loss has been observed as being controlled by placebo.…”
Section: Obesity Treatment By Metformin-fluoxetine M Siavash Dastjerdmentioning
confidence: 99%
“…15 By blocking the membrane-uptake carrier that transports serotonin from the extracellular space to inside the serotonin nerve terminals, fluoxetine increases extracellular concentrations of serotonin and amplifies signals sent by serotonin neurons. Because serotonin neurons are widespread in the central nervous system, the functional consequences of blocking serotonin uptake are diverse; this includes symptoms such as decreased food intake, altered food selection and endocrine changes.…”
Section: Obesity Treatment By Metformin-fluoxetine M Siavash Dastjerdmentioning
confidence: 99%
“…Vários trabalhos demonstram que até 70% de uma dose de femproporex pode se biotransformar no organismo, em anfetamina livre (Cody, 2002;Kraemer, Maurer, 2002;Musshoff, 2000;Cody, Valtier, 1999;Cody, Valtier, 1996;Sznelwar, 1975). Apesar disso e de ser controlado por legislação específica (Brasil, 1997), vários trabalhos demonstram que este fármaco tem sido amplamente utilizado, não somente como inibidor do apetite (Halpern, Mancini, 2003;Rodrigues et al, 2002), mas também como estimulante da vigília (INCB, 1998;Silva et al, 1998;Lopes et al, 1997;Nappo, Oliveira, Morosini, 1994;Nappo, 1992).…”
Section: Introductionunclassified